Mengulas Regulasi Terkait Upaya Penanggulangan Banjir Di Kota Padang - Fitri Dwi Nurmaliza; Ria Yusnita (CV. ITTC INDONESIA, 2024)
Talking about the floods that have occurred in Padang city in the last four years (2020-2024), many of them are caused by extreme weather that often changes, which makes it difficult to predict weather that can pose a flood risk. The main cause of flooding is that there is a drainage system that is not optimal and is also influenced by people's behavior in disposing of garbage, and the lack of government supervision is also one of the factors for flooding. Lack of supervision in the transfer of land functions, logging, implementation of infiltration area regulations and licensing of disaster-prone areas. The government said all of this was due to a limited government budget, so a problem formulation emerged: 1) How are regulations related to flood management in the city of Padang; 2) What are the factors inhibiting the difficulty of implementing regulations related to flood management efforts in the city of Padang. To answer this problem, a type of normative juridical research is used in this journal to find and review Padang City laws related to flooding so that conclusions are obtained: 1) regulations related to flood management in the city of Padang based on Law Number 24 of 2007 according to article 1 paragraph 6 of Government Regulation No. 21 of 2008 concerning the Implementation of Disaster Management, namely a series of efforts to reduce disaster risks, both through physical development and public education and capacity building to deal with disaster threats. Factors inhibiting the difficulty of implementing regulations related to flood management efforts in Padang city are due to a lack of coordination between agencies and the involvement of various institutions as well as different departments that may not be well coordinated in flood prevention and mitigation efforts.